Minimization of electro-mechanical interaction with posicast strategies for more-electric aircraft applications - Ahumada, C.; Garvey, Seamus D.; Yang, T.; Kulsangcharoen, P.; Wheeler, Patrick; Morvan, Herve (2016)
This paper studies strategies to minimize the electromechanical interaction (EMI) within aircraft power systems. With the growth of electrical power on-board aircraft, the interaction between the electrical systems and the engine core will become significant. The behaviour of electrical loads (on/off, transient etc.) will have significant impacts on the engine shaft, such as producing transient vibrations, creating stability problems and reducing the efficiency etc. To avoid these problems, an advanced electrical power management system (PMS) is required. This paper introduces novel loading methods for PMS applications to minimize the interactions between electrical and mechanical systems. The strategies, referred as Single Level Multi-edge Switching Loads (SLME), Multilevel Loading (MLL), and Multi-load Single Level Multi-edge Switching Loads (MSLME) are developed based on the Posicast method. An insight look of the developed technique has been studied using the zero-pole root locus. It is demonstrated that the excited poles in the system are cancelled by the addition of zeros, and thus supressed the EMI vibrations.